Studies on Adsorption of Phenol onto Ordered Mesoporous Carbon Prepared by Evaporation-Induced Triconstituent Co-assembly Method - Zhang, Tian-Dong; Zhou, Bo; Zeng, Xiao-Ying; Zhe, Wei; Zhang, Li-Li; Du, Yong-Fang; Zhang, Zhi-Dan; Yang, Jun (Asian Journal of Chemistry, 2012)
Highly ordered mesoporous carbon with complementary pores was prepared by evaporation-induced triconstituent co-assembly method. The adsorption isotherms were determined from the batch tests during which the effects of initial phenol concentration (25-1200 mg/L) were investigated. Both Langmuir and Freundlich isotherm models were developed and then compared. The equilibrium data were best represented by Langmuir isotherm model, showing maximum monolayer adsorption capacity of 480 mg/g which is two times higher than that of the activated carbon. The results showed that the prepared ordered mesoporous carbon is the suitable adsorbent for removal of phenol from aqueous solutions.